Carbon monoxide separation: past, present and future - POLAT, SEVGİ (My University, 2023)
This review discusses the developments in CO separation techniques in the last few decades and the gaps in knowledge it leaves, as well as sources of CO, both traditional and emerging, which would benefit from improved CO separation.
Keywords: Kimya Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, KİMYASAL; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, CHEMICAL; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences